Les Parisiennes. - Achard, Marcel, 1899-1974; Bauër, Gérard, 188-1967; Bory, Jean-Louis, 1919-1979; Breffort, Alexandre 1901-1971; Cassou, Jean, 1897-1986; Cocteau, Jean, 1889-1963; Cogniat, Raymond, 1896-1977; Deval, Jacques; Giraud, Robert; Groussard, Serge, 1921-2016; Géraldy, Paul, 1885-1983; Monier, Henri; et al. (Paris : Musée Galliera, 1958)
Adnet, Françoise ; Alaux, Jean-Pierre ; Alde, Yvette ; Ambrogiani, Pierre ; Ardenne, Lucien ; Ardissonne, Yolande ; Baboulene, Eugène ; Bellias, Richard ; Bezombes, Roger ; Pecq, Andrée Bordeaux Le ; Braig, Paul ; Brayer, Yves ; Bret, François ; Brusset, Jean-Paul ; Buffet, Bernard ; Cadiou, Henri ; Caillaud, Aristide ; Capron, Jean-Pierre ; Carréga, Nicolas ; Carton, Jean ; Carzou, Jean ; Cassarini, Jean ; Charlot, Paul ; Charon, Guy ; Chièze, Pierre ; Commere, Jean ; Déchelette, L.-Auguste ; Deman, Albert ; Desnoyer, François ; Despierre, Jacques ; Durel, Auguste ; Fleury, Camille ; Fontanarosa, Lucien ; Fougeron, André ; Tsugouharu ; Fusaro, Jean ; Gall, François ; de Gallard, Michel ; Gibert, Lucien ; Gili, Marcel ; Gimond, Marcel ; Godard, Gabriel ; Goerg, Edouard ; Grau-Sala, Emile ; Guignebert, Vincent ; Guiramand, Paul ; Hambourg, André ; Henry, Pierre ; Heraut, Henri ; Hilaire, Camille ; Janerand, Daniel Du ; Kretz, Léopold ; Labonne, Michel ; Lauzero, Albert ; Lefranc, Jules ; Lelong, Pierre ; Lepape, Claude ; Lersy, Roger ; Lhote, André ; Avoy, Edouard Mac ; Mané-Katz, Mané ; Mazot, Louis ; Montané, Roger ; Nakache, Armand ; Neillot, Louis ; Noyer, Philippe ; Oudot, Georges ; Papart, Max ; Planson, André ; Pollet, Jean ; Pressmane, Joseph ; Persan, Jean Raffy Le ; Salès, François ; Savin, Maurice ; Sekiguchi, Shungo ; Serveau, Clément ; Simon-Auguste, Simon ; Smith, Francis ; Térechkovitch, Kostia ; Therme, Henri ; Thiout, Jacques ; Ubeda, Agustin ; van Dongen, Kees ; Verdier, Maurice ; Vertès, Marcel ; Vignoles, André ; Vinay, Jean ; Volti, Antonicci ; Weisbuch, Claude ; Zendel, Gabriel
biografie
Les Parisiennes, Musée Galliera, Paris, mars-avril-mai 1958
Frans
boek